2020
DOI: 10.1002/pits.22425
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of increased rates of autism in U.S. public schools

Abstract: This study is intended to enhance our understanding of the dramatic increase in autism prevalence rates across the United States. A robust national and multistate sample of children and youth (5-22 years of age) was gathered and analyzed, using visual and statistical analysis of autism eligibility over a 15-to 17-year period. Although the impact of environmental or genetic influences cannot be entirely ruled out, we identified significant shifts in eligibility trends that substantially contribute to the remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
2
19
0
1
Order By: Relevance
“…The study found that the prevalence rate of autism based on clinical diagnostic criteria in China is 59.8 per 10,000, which is lower than that of 820 per 10,000 abroad and also lower than that of other countries in the world. This finding is similar to that of Chiarotti [9], the median prevalence rate of autism in Europe is 61.9 per 10,000 [10], the prevalence rate of autism in the USA is 110 per 10,000 [11], 264 per 10,000 people in South Korea have autism [12], and 181 autism per 10,000 people in Japan [13].…”
Section: There Are Significant Differences In Autism and Prevalence Of Autism Between Men And Womensupporting
confidence: 85%
“…The study found that the prevalence rate of autism based on clinical diagnostic criteria in China is 59.8 per 10,000, which is lower than that of 820 per 10,000 abroad and also lower than that of other countries in the world. This finding is similar to that of Chiarotti [9], the median prevalence rate of autism in Europe is 61.9 per 10,000 [10], the prevalence rate of autism in the USA is 110 per 10,000 [11], 264 per 10,000 people in South Korea have autism [12], and 181 autism per 10,000 people in Japan [13].…”
Section: There Are Significant Differences In Autism and Prevalence Of Autism Between Men And Womensupporting
confidence: 85%
“…Students who displayed lower cognitive functioning were also not identified as having a cognitive impairment but were more likely to be identified as AU. This aligns with the historical trends and the decrease in the assumption that to receive an educational diagnosis of AU, students also must be identified with cognitive impairment (Cardinal et al, 2021;Polyak et al, 2015;Rubenstein et al, 2018). Additionally, students who came into the evaluation with previous eligibility in YCDD -Communication were 7.22 times more likely to be identified as AU.…”
Section: Discussionsupporting
confidence: 64%
“…During that period, students with ASD between those ages rose from 0.9% (455,000) to 1.5% (762,000), representing a 66.6% increase of students with ASD enrollment in public schools [ 6 ]. Cardinal et al [ 7 ] point out that the rate of ASD growth has proceeded at a statically significant higher rate than have national changes in special education.…”
Section: Introductionmentioning
confidence: 99%